Indigenous medicinal usage of family Solanaceae and Polygonaceae in Uri, Baramulla, Jammu and Kashmir - Jan, Muatasim; Mir, Tawseef Ahmad; Khare, Rakesh Kumar (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Kashmir Himalaya is known for it’s dense and diverse vegetation. People here have gained immense knowledge regarding the use of medicinal plants for the treatment of different ailments. The present study attempts to explore and document the medicinal plants belonging to the family Solanaceae and Polygonaceae used against different ailments by tribal communities of Uri, Baramulla, Jammu and Kashmir. Data was collected by using semi structured interviews and group discussions. Besides local tribal communities of Gujjar and Bakerwal, herbal healers and local knowledgeable persons were consulted during the course of the study. During the study, a total of 25 plants were reported with a species contribution of 10 and 15 of Solanaceae and Polygonaceae respectively. The study revealed that either the whole plant or some plant parts are used as remedies against different ailments in the area.